2016
DOI: 10.1186/s12913-016-1894-4
|View full text |Cite
|
Sign up to set email alerts
|

Advancing services for adult ADHD: the development of the ADHD Star as a framework for multidisciplinary interventions

Abstract: BackgroundAttention Deficit Hyperactivity Disorder is prevalent in adulthood, resulting in serious impairment across multiple domains of living. Despite clinical guidance recommendations, the relative infancy of research on service provision for adults with ADHD, along with the evidence transfer gap, means that there is a lack of specific frameworks for service delivery. Igniting research and developing service delivery frameworks within adult ADHD is an essential step in the provision of effective services fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Involvement of various stakeholders in discussions about these issues through community‐based participatory research approaches will be important to developing a robust understanding of an acceptable clinical research agenda to the ADHD community and will help researchers ensure this work is less likely to be framed in ways that perpetuate stigma. In particular, while there is recognition of the need to involve ADHD community members as stakeholders, there is relatively little work using formally‐defined methods (but see Adamou et al., 2016 ) such as participatory action research methods (Shamrova & Cummings, 2017 ) or cultural consensus modeling (Ulijaszek, 2013 ) that would allow individuals with ADHD and their family members to actively participate in defining research questions, planning and conducting studies, and interpreting and disseminating findings. Ultimately, novel early identification and intervention approaches will only be widely adopted if they are welcomed by individuals with ADHD and their families.…”
Section: Ethical Issues and Community Engagementmentioning
confidence: 99%
“…Involvement of various stakeholders in discussions about these issues through community‐based participatory research approaches will be important to developing a robust understanding of an acceptable clinical research agenda to the ADHD community and will help researchers ensure this work is less likely to be framed in ways that perpetuate stigma. In particular, while there is recognition of the need to involve ADHD community members as stakeholders, there is relatively little work using formally‐defined methods (but see Adamou et al., 2016 ) such as participatory action research methods (Shamrova & Cummings, 2017 ) or cultural consensus modeling (Ulijaszek, 2013 ) that would allow individuals with ADHD and their family members to actively participate in defining research questions, planning and conducting studies, and interpreting and disseminating findings. Ultimately, novel early identification and intervention approaches will only be widely adopted if they are welcomed by individuals with ADHD and their families.…”
Section: Ethical Issues and Community Engagementmentioning
confidence: 99%
“…From previous work, we found that the framework proposed by the ADHD Star can be a useful guide to multidisciplinary interventions based on the ADHD Star domains 'Focus and Attention', 'Friends and Social Life', 'Physical Health', 'How you Feel' "Understanding your ADHD", "Organising yourself", "Thinking and reacting" and "Meaningful use of time" [54]. To this framework, the Occupational Therapy Models of Practice can be deployed using the different frames of reference depending on the needs of the individual.…”
Section: Occupational Therapy Approaches and Adult Adhdmentioning
confidence: 99%
“…The relatively recent widespread recognition that ADHD often persists across the lifespan, has left adult service providers working out how best to meet this need, which encompasses up to three generations of undiagnosed adults with ADHD. Various models of care have emerged and are still evolving [9,10], but to date the relatively few established adult ADHD services within the National Health Service (NHS) in the United Kingdom (UK) have generally not been resourced sufficiently to meet the considerable need [11,12]. This problem likely exists in many other regions of the world.…”
Section: Introductionmentioning
confidence: 99%